Cost-benefit analysis of Light Emitting Diode (LED) lamp conversion in TUP-Taguig - Gacusan, Danilo M. (University of the Philippines Diliman, 2012)
This paper evaluates and analyzes the cost of not using LED lamps. It also likewise studies the benefit of using this kind of technology and the cost it entails in the target institution. TUP-Taguid is the subject of this study where the author is one of its faculty members pursuing the Master in Technology Management in the University of the Philippines-Diliman through the DOST scholarship. Would it be beneficial for the University to use LED as its lighting system? Would replacing the fluorescent lighting system with LED lighting solve the University's problem of high maintenance cost of fluorescent bulb and high cost of electric bill? These are some issues that need some special attention and should be addressed by this research study. Light Emitting Diode, which is conveniently called as LED lights in electronic term, is a semi conductor light that emits light as soon as an electric current is applied to it. They are extensively used as indicator lights on electronic devices and also in higher power applications as in case of flashlights and area lighting. LED technology has taken the world to an innovative stage of development as it is very useful in conservation of energy and pollution. Some of the important advantages of the bulb are- 1. LED lights are more efficient when compared to the conventional bulbs and tube lights. They produce more light per watt against an incandescent bulb and this facet makes it very useful when used in battery powered or energy-saving devices. 2. This technology has the capacity of emitting various colors of light without the use of colors filters that traditional lighting methods require, thus saving initial costs. 3. Due to their small size, they can be easily placed and they also light up very quickly and achieve full brightness in microseconds. 4. These LED light have a better cycling life as compare to glowing bulbs and also radiate much less heat in the process of switching on and off. 5. They have a better life span around 25,000 to 50,000 hours of useful life and LEDs mostly fail by dimming over time, rather than the abrupt burn-out of incandescent bulbs as in comparison to incandescent lights. 6. These lights are shock resistant and the solid package of the LED can be designed to focus its light. The fact that they are non toxic (do not complain mercury) also favors the application of these bulbs. However, withstanding all the advantages, there are certain short comings faced by these LED lights as well. They are listed below - 1. As compared to bright bulbs the LEDs are much more expensive and its execution largely depends on the ambient temperature of the operating environment. They require sufficient heat sinking in order to make it stronger. 2. These LEDs are also voltage sensitive and one needs to be vigilant as they involve series of resistors or current-regulated power supplies. As they work on the mechanism of area light source, it becomes difficult for them to operate in spherical light field. 3. Of recent it is being observed by the scientists that blue and cool white LEDs emit blue light hazard that is unsafe for eyes. The cool white LED lights should not be used for outdoor lighting near astronomical observatories. Together these lights have certain limitations that are termed as blue pollution. This study compares the LED technology to the CFL technology in terms of the financial benefits as well as other benefits that concern the care of environment. A typical LED bulb can last up to 15 years without needing to be changed. They are not as versatile in traditional light fixtures, however, and are generally more expensive than compact fluorescents. Converting to LED lighting allows consumers to conserve energy and save a huge amount of money on maintenance and energy costs. LED light bulbs will eventually be what we use to replace incandescent bulbs - CFLs are a temporary solution to energy-efficient lighting. The reason LEDs have not yet displaced CFLs from the market are twofold : the first generation LED bulbs had a narrow and focused light beam, and the cost of the LED bulbs was too high. Recent developments in LED technology, however, have been addressing these issues. LEDs have been 'clustered' to provide more light, and mounted within diffuser lenses which spread the light across a wider area. And advancements in manufacturing technology have driven the prices down to a level where LED bulbs are most cost-effective than CFLs or incandescent bulbs. This trend is continuing, with LED bulbs being designed for more applications while the prices are going down over time. Table 1 up to Table 4 show the comparison charts between the LED, CFL and Fluorescent lamps in terms of energy efficiency and energy cost, light output and the environmental impact and some important facts about these three types of lamps. This study also includes national laws governing the disposal of busted fluorescent bulbs, RA 6069 or the Toxic substances, Hazardous and Nuclear Waste Control Act of 1990 and RA 2003, The Ecological Solid Waste Management Act. The ultimate goal of RA 6069 or the Toxic substances, Hazardous and Nuclear Waste Control Act of 1990 is to protect people and the environment from risks that are coming from industrial chemicals and chemical substances. The law sets the framework for the country to manage and control the importation, manufacture, processing, distribution, use, transport, treatment, and disposal of toxic, hazardous and nuclear wastes. RA 2003, The Ecological Solid Waste Management Act is the law which assigns the task of different stakeholders in disposing of wastes. Apart from that, it also contains provisions about recycling. There is no explicit mention of lamp wastes in the law's provision and implementing rules and regulations. It is classified, however, in special wastes including paint thinners, household batteries, lead-acid batteries, spray canisters, including consumer electronic goods like radios, stereos and television sets.